Infecção latente por Mycobacterium tuberculosis entre contatos de pacientes com tuberculose pulmonar cavitária e não cavitária - Molino, Lucilia Pereira Dutra (2009)
The tuberculosis continues to represent a severe worldwide public health issue, particularly in developing countries. Besides early diagnosis and therapy, one of the great challenges for its control is the scarce knowledge available about the transmission mechanisms and the related risks. The retrospective cohort described in this study aims to evaluate the risk of Mycobacterium tuberculosis infection, measured by tuberculin skin testing, in contacts of patients with cavitary and noncavitary pulmonary tuberculosis. Identification and screening of index cases between july/2003 and december/2007 was performed based on analysis of two databases: National information system of disease notification and TB notes. Only index cases, with age above 18 years old, living at Cariacica, Serra, Vila Velha and Vitoria cities were screened. Demographic, clinical and laboratory informations of the index cases and contact informations were captured from the medical charts. Bacteriological confirmation based on mycobacterial cultures was captured from TB notes database. among the 1662 index cases identified, 320 met the inclusion criteria: 154 (48,1%) with cavitary disease (C group) and 166 (51,9%) with non-cavitary disease (NC group) based on chest xray. among these 320 index cases, 1257 contacts were identified. most cases of C and NC groups denied previous contact with tuberculosis: 70,2% and 60,1%, respectively. index cases reported cough ranging between 0 and 980 days; mean of 93,5 and median of 60 days; 25 and 75 percentis were 30 and 90 days, respectively. period of cough, which represent time of disease, was higher in the c group (p=0,01, OR 1,82, IC 95%:2,8-13,5) when the threshold was 60 days. higher number of positive sputum smear patients was observed in the C group (p <0,00, OR=5,86, IC 95%: 2,8-13,5). among the 1257 enrolled contacts, 555 (44%) were contacts of the C group and 702 (56%) of the NC group patients. both groups were similar regarding gender, age and chest xray images. however, more reactors to tuberculin skin testing (PPD ≥ 10 mm) were found among contacts of C group: 48% versus 40,6% (p= 0,009, OR1,35, IC 95% 1,07-1,7 ). Taking into account images observed in chest xray, M tuberculosis infection rate was 1,7 higher among contacts of cavitary in comparison with non-cavitary patients. After logistic regression analysis this association was statistically significant for two variables: period of cough ≥ 30 days (p=0, 0007OR=3, 20, IC 95%: 1, 5-8.6,) and positivity of sputum smears (p=0, 0039 OR=2, 47, IC 95: 1, 24-4, 81). Positivity of sputum smears was also related to the presence of cavitary disease. Index cases included in C group had 5, 86 more chance of having positive sputum smear (IC 95%: 2, 8-13, 5). Using infection prevalence rate of 30% or more as the threshold for transmission analysis, the three following variables were related to infection transmission to contacts: period of cough, cavitary disease and positive sputum smear. It was concluded that: a period of cough ≥30 days was associated with TB infection; smear positivity was associated with a higher chance of infection among contacts. The association between cavitary disease and TB infection transmission to contacts was marginally statistically significant.